1993
DOI: 10.1111/j.1469-8137.1993.tb03839.x
|View full text |Cite
|
Sign up to set email alerts
|

Symbiotic exchange of carbon and phosphorus between cucumber and three arbuscular mycorrhizal fungi

Abstract: SUMMARYCucumber {Cucumis sativus L.) was grown in an irradiated soil:sand mixture in PVC tubes containing a root compartment, a hyphal compartment and a hyphal ''P-labelling compartment. At 23 d from sowmg 20 / Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
125
0
2

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(133 citation statements)
references
References 17 publications
6
125
0
2
Order By: Relevance
“…They suggested that P transport was limited by processes involved in hyphal translocation and\or transfer across the symbiotic interface rather than hyphal P uptake itself. Scutellospora calospora accumulated large amounts of $#P into its hyphae but transported little to the host plant Cucumis sativus (Pearson & Jakobsen, 1993). By contrast, we have shown large increases in P uptake and plant growth in Allium porrum colonized by S. calospora and Glomus sp. '…”
mentioning
confidence: 66%
“…They suggested that P transport was limited by processes involved in hyphal translocation and\or transfer across the symbiotic interface rather than hyphal P uptake itself. Scutellospora calospora accumulated large amounts of $#P into its hyphae but transported little to the host plant Cucumis sativus (Pearson & Jakobsen, 1993). By contrast, we have shown large increases in P uptake and plant growth in Allium porrum colonized by S. calospora and Glomus sp. '…”
mentioning
confidence: 66%
“…There is increasing evidence, for example, that the diversity of species of AMF (as measured by DNA sequencing in some cases) in the plant\soil environment might determine plant community structure (Clapp et al, 1995 ;Helgason et al, 1998 ;Van der Heijden et al, 1998a,b). This might reflect the unique development and life-cycle requirements of these fungi as indicated in recent studies using species of AMF from different genera (Jakobsen et al, 1992a,b ;Pearson & Jakobsen, 1993 ;Boddington & Dodd, 1998). Despite this, the majority of studies on AMF use only species of Glomus (Abbott et al, 1984 ;Amijee et al, 1993 ;Zhao et al, 1997).…”
Section: mentioning
confidence: 99%
“…The use of alkaline phosphatase activity, localized in the vacuole of the intra-radical mycelium of AMF (Gianinazzi et al, 1979), as a potential marker for phosphate metabolism in mycorrhizas is still equivocal. Other mechanisms might also be involved in phosphate metabolism that affect the uptake, translocation and\or transfer of phosphate to the plant via the fungal mycelium (Jakobsen et al, 1992a,b ;Pearson & Jakobsen, 1993 ;Harrison & Van Buuren, 1996 ;Boddington & Dodd, 1998). However, the alkaline phosphatase in the extra-radical mycelium might be an effective marker for phosphate metabolism in studies on AMF, in contrast to that in the intraradical mycelium (Dodd, 1994).…”
Section: mentioning
confidence: 99%
“…Conclusions about whether ectomycorrhizas generally have higher P uptake efficiencies than arbuscular mycorrhizas must await comparisons between larger numbers of species of each type. Obviously a considerable amount of variability, such as that found by Pearson & Jakobsen (1993), is to be expected within each of the mycorrhizal groups.…”
Section: mentioning
confidence: 99%
“…Jones et al (1991) calculated that willow ectomycorrhizal with Thelephora terrestris took up more P per unit of C than did NM plants. Pearson & Jakobsen (1993) compared the efficiency of three AM fungi by measuring hyphal "%C use per unit $#P transported and below-ground "%C use per unit $#P transported. Both Tinker et al (1994) with ECM willow and Raju et al (1990) with AM sorghum calculated costs and benefits to the mycorrhizal plant in terms of C. Tinker et al (1994) determined that ECM willow converted 85 % of the extra C fixed into shoot biomass ( l C-use efficiency).…”
mentioning
confidence: 99%